2005
DOI: 10.1002/jsfa.2146
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and nutritive value of peach palm (Bactris gasipaes Kunth) in rats

Abstract: The peach palm (Bactris gasipaes Kunth) is the starchy fruit of a palm tree widely cultivated in Central and South America. The present study aimed at determining its chemical composition and its nutritive value in rats. The average chemical composition of 17 samples was as follows: 410 g kg −1 water and, in g kg −1 of dry matter (DM), 54 g crude protein, 114 g oil, 39 g neutral detergent fibre, 716 g starch, 21 g sugars and 18 g ash. The main variability was observed for the oil (60-180 g kg −1 DM) and starch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
0
24
1
6
Order By: Relevance
“…Dry matter was strongly correlated with texture both in raw and cooked peach palm. It is also correlated with fat and protein content Rodriguez et al 2009), though starch content was found to be inversely correlated with oil (Leterme et al 2005;Giraldo et al 2009). Carrera (1999) studied the chemical and physical properties of starches isolated from six Peruvian peach palm phenotypes.…”
Section: Nutritional Compositionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dry matter was strongly correlated with texture both in raw and cooked peach palm. It is also correlated with fat and protein content Rodriguez et al 2009), though starch content was found to be inversely correlated with oil (Leterme et al 2005;Giraldo et al 2009). Carrera (1999) studied the chemical and physical properties of starches isolated from six Peruvian peach palm phenotypes.…”
Section: Nutritional Compositionmentioning
confidence: 99%
“…Fruit diameter varies from 1 to 9 cm, and mean fruit weight normally ranges from 20 to 65 g, though fruits may weigh up to 225 g ( Fig. 3; Arkcoll and Aguiar 1984;Leterme et al 2005;Rivera 2009). …”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Su distribución se extiende desde Panamá hasta Bolivia, en regiones con una altitud inferior a 1.000 msnm, con precipitaciones anuales entre 2.000 y 5.000 mm y temperatura media anual de más de 22 °C (Leterme et al, 2005;Pinzón, Zapata, & Ordóñez, 2015). Pertenece a la familia de las palmáceas (Arecaceae) y es conocido con nombres comunes de acuerdo con la región donde se consume: chontaduro, pejibaye, cachipay, peripao y pupuña macanilla, entre otros (Restrepo, Vinasco, & Estupiñán, 2012).…”
Section: Introductionunclassified